1911 Del. Laws 324, Of Fish, Oysters and Game, § 8 - (:unkn) unknown (General Publisher, 1911)
Prohibited the unlawful shooting or killing of any birds or animals protected by laws of the state using any device, swivel, punt gun, or any gun other than shouldered weapons raised at arm's length. Also prohibited hunting with the aid of artificial light or lantern, dog, or dogs equipped with bells or other noise-producing device.
--
Keywords: HUNTING REGULATION